Relationships between arts participation, social cohesion, and well-being: an integrative review of evidence - Jill Sonke; Virginia Pesata; Aaron Colverson; Aaron Colverson; Jane Morgan-Daniel; Alexandra K. Rodriguez; Alexandra K. Rodriguez; Gray Davidson Carroll; Shanaé Burch; Abel Abraham; Seher Akram; Stefany Marjani; et al. (Frontiers in Public Health)
IntroductionArts and cultural strategies have increasingly been engaged by the public health sector to enhance social cohesion, health, and well-being, as well as to address the significant health risks posed by social isolation and loneliness. While numerous studies document relationships between arts participation and social cohesion or well-being, few studies have investigated the relationships between all three and, to date, no evidence synthesis has been conducted on this topic.MethodsTo address this gap, this integrative review aimed to identify, describe, and synthesize research on arts participation, social cohesion, and well-being in a community context by addressing the question: what is the evidence base regarding relationships between arts participation, social cohesion, and well-being? Literature searches were conducted using 10 databases, and analyses included descriptive statistics, thematic analysis and content-mechanism-outcomes analysis.ResultsA total of 18 articles - 16 original research articles and two reviews – from 12 countries met inclusion criteria. Results provide insights on modes and forms of arts participation used to address social cohesion and well-being and suggest that SC may function as a mechanism for enhancing community well-being. Themes highlight the value of physical engagement in community spaces and culturally-rooted programming, the virtuous cycle of commitment and benefit that can be cultivated by co-creation and social relationships, and how social cohesion can serve as a mechanism for enhancing well-being.DiscussionThis study’s insights related to how the arts can build social cohesion and, in turn, enhance well-being can guide design of community-based programs. Prospective studies are needed to test these relationships as well as the potential role of social cohesion as a mechanism for building well-being in communities through arts participation.